Adoption Decision and Sustainable Utilization of Soil Conservation Technologies: Empirical Evidence from North West Ethiopia - Legese, Kassaye Gurebiyaw; Melese, Taye; Mire, Tadie; Birara, Abebe; Eniyew, Kefale (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Soil is a crucial and precious natural resource that govern numerous ecological processes. However, in Ethiopia particularly in north Gondar zone, soil erosion is a severe problem and a major cause of the decline of agricultural productivity. The adoption and diffusion of soil and water conservation practices (SWC), as a way to tackle this challenge, has become an important issue in the development policy agenda in the zone. Therefore, this study was to identify factors affecting Soil conservation investments in the North Gondar zone. Data was collected through interviewed schedule, filed observation and focus group discussion. The multistage sampling technique was employed to select 206 sample households. Both descriptive and econometrics model was used to analyze the collected data. A multivariate profit (MPV) model was used to analyze the effect of demographic, socioeconomic, market, institutional and biophysical related factors on the interdependent investment decisions of SWC practices using household survey. The MPV model analysis indicates that farmers invest a combination of practices at parcel level by considering substitution and complementarity effects of the practices. The results also revealed that age of household heads, literacy status of household heads, off-farm activity, distance of farmlands from homesteads, tropical livestock unit, and access to training were influence farmers’ investments in SWC practices. The overall results indicate that the identified physical, socioeconomic, and institutional factors influence promote or hinder investments in SWC practice so, policymakers should take into consideration these various factors in designing and implementing SWC policies and Programmers.